Outcome after colorectal full-thickness resection and management of recurrence - Mueller, Julius; Miedtke, Valentin; Kuellmer, Armin; Schiemer, Moritz; Bettinger, Dominik; Thimme, Robert; Schmidt, Arthur (Endoscopy International Open, 2024)
Background and study aims Endoscopic full-thickness resection (eFTR) allows treatment of “difficult to resect” lesions not amenable to conventional endoscopic methods. Efficacy and safety of the system have already been proven in numerous studies. Follow-up data on outcome of colorectal eFTR and management of recurrences are still rare.Patients and methods All patients undergoing colorectal eFTR at our institution with at least one endoscopic follow-up examination were retrospectively analyzed. The primary endpoint was the rate of recurrent or residual lesions (RRLs) and the secondary endpoint was the rate of late adverse events (AEs). We further aimed to identify risk factors for RRLs and to describe their management.Results Between November 2014 and 2021, 141 patients underwent eFTR at University Medical Center Freiburg. Ninety-one patients fulfilled the inclusion criteria. Indications for eFTR were non-lifting adenoma (n = 65), subepithelial tumors (n = 18) and early carcinoma (n = 8). The median follow-up period was 17 months (range, 2–86). The overall RRL rate was 9.9% (9/91). A significant proportion of RRLs (6/9, 66%) were detected late. All RRLs occurred in the group of non-lifting adenoma, corresponding to a RRL rate of 13.8% in this subgroup. Thirty-three percent (3/9) were initially treated by hybrid eFTR. Of the RRLs, 66.6% could were successfully treated endoscopically. On χ2 analysis, the hybrid eFTR technique (P = 0.006) was associated with a higher rate of RRL. No late AEs occurred.Conclusions The rate of RRL after colorectal eFTR is low and the majority could be treated endoscopically. For non-lifting adenomas and early carcinomas, close follow-up is mandatory to detect late recurrence. Long-term outcomes after hybrid eFTR need further investigation.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Endoscopic resection (polypectomy, ESD, EMRc, ...); Colorectal cancer